(3GdCWQ GdTQYjI hGdafjI dHhQUI GdChQGb GdeGdjI hBdjGJ GdQbGHI GdbGfhfjI YdjgG (B/s - (3YHO GdJhGH, eMeO Mdejs ((3GdbGgQI(B: s (3OGQ GdacQ GdYQHj(B, s, 2012)
(3GdSjGSGJ GdeGdjI GdMOjKI hfTCI CShGb GdChQGb GdeGdjI(B- (3GdEWGQ GdTQYj dHhQUI GdChQGb GdeGdjI(B- (3adSaI GdeGd aj GdCOjGf GdSeGhjI bHd GdESdGe(B-(3adSaI GdESdGe aj JfejI GdeGd(B- (3GdEWGQ Gdafj dYed HhQUI GdChQGb GdeGdjI(B- (3EOGQI GdHhQUI(B- (3cjajI Yed Shb GdChQGb GdeGdjI(B-(3JfTjW GdHhQUI(B- (3GdQHW Hjf GdHhQUGJ(B- (3BdjGJ GdQbGHI GdbGfhfjI Ydi GdHhQUIs
Keywords: (3GdChQGb GdeGdjIs; (3GdHhQUGJs; (3GdQbGHI GdeGdjIs